2012
DOI: 10.1111/cge.12036
|View full text |Cite
|
Sign up to set email alerts
|

Monozygotic twins discordant for submicroscopic chromosomal anomalies in 2p25.3 region detected by array CGH

Abstract: Although discordant phenotypes in monozygotic twins with developmental disorder are not an exception, underlying genetic discordance is rarely reported. Here, we report on the clinical and cytogenetic details of 4-year-old female monozygotic twins with discordant phenotypes. Twin 1 exhibited global developmental delay, overweight and hyperactivity. Twin 2 had an autistic spectrum disorder. Molecular karyotyping in twin 1 identified a 2p25.3 deletion, further confirmed by Fluorescence in situ hybridization (FIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 27 publications
(34 reference statements)
1
35
0
2
Order By: Relevance
“…The four patients with a 2p25.3 duplication and disruption of the MYT1L gene show significant signs of schizophrenia and paranoia, 12,13,15 whereas a girl, mosaic for 2p25.3 deletion cells, 2p25.3 duplication cells, and normal cells, only shows signs of autism. 14 Here we report another 20 patients with either a 2p25.3 microdeletion or microduplication, all of whom share a (partial) aberration in MYT1L, as well as two patients with a de novo loss-of-function mutation in MYT1L (patients 14 and 15). Furthermore, in two patients (patients 9 and 10), MYT1L is the only deleted gene.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The four patients with a 2p25.3 duplication and disruption of the MYT1L gene show significant signs of schizophrenia and paranoia, 12,13,15 whereas a girl, mosaic for 2p25.3 deletion cells, 2p25.3 duplication cells, and normal cells, only shows signs of autism. 14 Here we report another 20 patients with either a 2p25.3 microdeletion or microduplication, all of whom share a (partial) aberration in MYT1L, as well as two patients with a de novo loss-of-function mutation in MYT1L (patients 14 and 15). Furthermore, in two patients (patients 9 and 10), MYT1L is the only deleted gene.…”
Section: Discussionmentioning
confidence: 79%
“…1,2,11,14,16 Obesity or overweight is noted in 17 patients (10 of 14 patients with a deletion, 5 of 6 with a duplication, and 2 of 2 with a point mutation) and has an onset during (late) childhood (Supplementary Table S1 online). Other prevalent symptoms are a wide range of behavioral problems (11 of 14 patients with a deletion, 6 of 6 with a duplication, and 2 of 2 with a point mutation), such as aggressive, autistiform, and hyperactive behavior; stereotypic hand movements; and sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…The PraderWilli-like phenotype, as reported by Becker et al, 6 has been described in the literature in eight other patients with 2pter deletion. 4,7,8 Pure 2pter deletion was reported by Stevens et al 7 in six adult patients with ID, obesity or overweightness, and/or square-shaped stature. A similar deletion encompassing the FAM110C, SHY3YL1, ACP1, FAM150B, TMEM18, C2ORF90, SNTG2, TPO, PXDN, and MYT1L genes was reported in four out of the six patients, whereas the two remaining patients presented with a smaller deletion encompassing the TPO, PXDN, and MYT1L genes for one and the PXDN and MYT1L genes for the other.…”
Section: Discussionmentioning
confidence: 86%
“…[1][2][3][4][5][6][7][8] Becker et al 6 reported a patient with a de novo pure 2p25.2 deletion, bilateral severe talipes equinovarus, pulmonary valve stenosis, nasal polyps, mild psychomotor retardation, and overweightness with food seeking behaviour. Several patients were then reported presenting with obesity, intellectual disability (ID), and 2p25 deletion.…”
Section: Introductionmentioning
confidence: 99%
“…The raw array CGH data (log 2 intensity ratios) were processed for CNV detection as proposed earlier [51,52]. The protocol was modified to achieve comprehensive data on CNVs according to intensity ratios values for 4 oligonucleotide and 2 interchangeable BAC probes.…”
Section: Methodsmentioning
confidence: 99%